Checkpoints of B cell differentiation: visualizing Ig-centric processes - Berkowska, Magdalena A.; van der Burg, Mirjam; van Dongen, Jacques J.M.; van Zelm, Menno C. (Annals of the New York Academy of Sciences, 2011)
The generation of antibody responses and B cell memory can only take place following multiple steps of differentiation. Key molecular processes during precursor B cell differentiation in bone marrow generate unique antibodies. These antibodies are further optimized via molecular modifications during immune responses in peripheral lymphoid organs. Multiple checkpoints ensure proper differentiation of precursor and mature B lymphocytes. Many of these checkpoints have been found disrupted in patients with a primary immunodeficiency. Based on studies in these patients and in mouse models, new insights have been generated in B cell differentiation and antibody responses. Still, in many patients with impaired antibody formation, it remains unclear how B cells are affected. In this perspective, we present 11 critical processes in B cell differentiation. We discuss how defects in these processes can result in impaired checkpoint selection and how they can be visualized in healthy subjects and patients with immunodeficiency or other immunological disease.